Anti-pollution flashover and anti-impact tempered glass insulator and processing technology thereof

Through the melting molding and multi -step tempered treatment process of specific formula materials, it is made into anti -flicker and anti -impact tempered glass insulator, which solves the problem of fragile, self -explosion and flicker flashing of existing tempered glass insulation, which significantly improves insulation performance and Line security.

CN119330588APending Publication Date: 2025-01-21PINGXIANG XINYUAN INSULATOR GRP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411444735.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing tempered glass insulators are fragile and self-destructive during use of power transmission lines, resulting in increased line maintenance costs and easy to appear in atmospheric environments, reducing insulation strength and affecting the normal operation of the power system.

Method used

Use specific formulas of silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, ceria, niobium trioxide, scandium trioxide, tungsten carbide, nano boron nitride and other materials to mix and melt to form a molten liquid, which is heated in nitrogen Formed in the environment, with the After that, primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment and secondary nitriding treatment are carried out. Finally, the iron cap, tempered glass parts and steel feet are glued together with adhesive to make anti-fouling flashover and impact-resistant products. Tempered glass insulator.

Benefits of technology

It significantly improves the anti-fouling flashover and impact resistance of tempered glass insulators, reduces fragility and self-explosion, reduces line maintenance costs, and improves insulation strength in the atmospheric environment, ensuring the normal operation of the power system and the safety of power supply.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-pollution flashover and anti-impact tempered glass insulator and a processing technology thereof.The processing technology comprises the steps that silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide and nano boron nitride are evenly mixed according to the formula ratio and fused, and fused liquid is obtained; then slowly injecting the molten liquid into a mold preheated in advance in a nitrogen environment, molding, and demolding to obtain a blank; carrying out primary nitriding treatment, pulsed magnetic field treatment, toughening treatment, heat treatment and secondary nitriding treatment to obtain a toughened glass part; and finally, binding the iron cap, the toughened glass piece and the steel foot into a whole by using an adhesive to obtain the toughened glass insulator. The toughened glass insulator has excellent anti-pollution flashover and anti-impact performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of insulator processing, and in particular relates to an anti-pollution flashover and impact-resistant tempered glass insulator and a processing technology thereof. Background Art

[0002] An insulator is a structural element used to separate and support various conductors in a power system, ensuring the insulation performance of high-voltage electrical equipment and preventing discharge between the metal structure of electrical equipment or electrical devices and the ground, thereby ensuring the normal operation and use of electrical equipment.

[0003] Insulators are usually made of glass or ceramic. Compared with ceramic insulators, glass insulators have the following advantages:

[0004] 1. High mechanical strength;

[0005] 2. Stable performance, not easy to age, better electrical performance;

[0006] 3. Few production processes, short production cycle, easy mechanization and automation production, high production efficiency;

[0007] 4. Glass insulators are transparent, and small cracks and various internal defects or damages can be easily found during external inspection;

[0008] 5. When there are defects in the glass insulator, it will automatically break and can be easily found. The iron cap and the remaining hammer still maintain a certain mechanical strength and hang on the line, so the line can continue to operate.

[0009] 6. Glass insulators are light in weight.

[0010] The glass insulators currently used are made of ordinary tempered glass, which is prepared by wind tempering. It is impossible to achieve uniform tempering effect on the glass, which makes the tempered glass insulators fragile and self-explosive during the use of transmission lines, resulting in increased line maintenance costs, increased manpower and material resources, and restricted the development and application of tempered glass insulators. Therefore, it is very necessary to improve the process to improve the impact resistance of tempered glass insulators.

[0011] In addition, under the influence of various factors such as the ground atmospheric environment, aging materials, leaf residues, salt spray, industrial pollutants, etc., the surface of the tempered glass insulator will inevitably be polluted. After a long period of accumulation, the sediment on the surface of the tempered glass insulator will form a dirt layer, and under the action of the electric field, a surface charge layer of a certain thickness will be formed, resulting in the non-uniformity of the electric field distribution, which greatly reduces the insulation strength of the insulator, causes corona discharge, and causes the arc to flash on the surface of the insulator. This phenomenon is called pollution flash. Pollution flash is extremely harmful. It will not only directly cause the breakdown of the insulator, but also form cascade discharge between the working electrical appliances and the lines, causing accidents and interference in the power system, affecting the normal operation and power supply safety of the power system. Therefore, it is also very necessary to improve the anti-pollution flash performance of tempered glass insulators. Summary of the invention

[0012] In view of the deficiencies in the prior art, the object of the present invention is to provide a pollution flashover proof and impact resistant tempered glass insulator and a processing technology thereof, so as to improve the pollution flashover proof and impact resistant performance of the tempered glass insulator.

[0013] In order to achieve the above object, the present invention adopts the following technical solution:

[0014] A processing technology for anti-pollution flashover and impact-resistant tempered glass insulators, the specific steps are as follows:

[0015] (1) firstly, uniformly mix silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide, and nano boron nitride in a formulated amount, and melt the mixture to obtain a molten liquid;

[0016] (2) then slowly injecting the molten liquid into a preheated mold under a nitrogen environment, forming, demolding, and obtaining a blank;

[0017] (3) primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, secondary nitriding treatment to obtain a tempered glass piece;

[0018] (4) Finally, the iron cap, the tempered glass piece and the steel foot are glued together using adhesive to obtain the tempered glass insulator.

[0019] Preferably, in step (1), the formula composition is, by weight: 60-70 parts of silicon dioxide, 8-10 parts of sodium carbonate, 5-6 parts of calcium oxide, 5-6 parts of magnesium oxide, 4-5 parts of cerium dioxide, 2-3 parts of niobium trioxide, 1-2 parts of scandium trioxide, 1-2 parts of tungsten carbide, and 1-2 parts of nano-boron nitride.

[0020] Preferably, in step (1), the melting temperature is 1300-1400° C., and the melting temperature is maintained for 30-40 minutes.

[0021] Preferably, in step (2), the mold is preheated to 700-800°C.

[0022] Preferably, in step (2), the molding temperature is 500-600° C. and the holding time is 60-70 minutes.

[0023] Preferably, in step (3), the specific method of the primary nitriding treatment is: in the nitriding furnace, ammonia is introduced, the temperature is raised to 500-520°C at 8-10°C / min, kept warm for 1-2 hours, the temperature is raised to 580-600°C at 2-3°C / min, kept warm for 2-3 hours, and cooled to room temperature with the furnace.

[0024] Preferably, in step (3), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field frequency 0.05-0.07 Hz, magnetic field 4-6 T, and treatment time 30-40 minutes.

[0025] Preferably, in step (3), the process conditions of the tempering treatment are: in a tempering machine, tempering is performed at a rotation speed of 150 to 200 r / min, the upper wind pressure is 0.1 to 0.12 MPa, and the lower wind pressure is 0.05 to 0.07 MPa.

[0026] Preferably, in step (3), the process flow of heat treatment is:

[0027] (a) Rotate at 280-300 r / min, heat at 7-8 °C / min to 700-720 °C, and keep warm for 30-40 minutes;

[0028] (b) rotating speed 220-250 r / min, cooling at 2-3°C / min to 640-660°C, keeping warm for 50-60 minutes;

[0029] (c) rotating at 180-200 r / min, heating at 5-6°C / min to 750-780°C, and keeping at this temperature for 60-80 minutes;

[0030] (d) Rotate at 220-250 r / min and keep warm for 2-3 hours;

[0031] (e) Cool naturally to room temperature.

[0032] Preferably, in step (3), the specific method of the secondary nitriding treatment is: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 550-580° C. at 5-6° C. / min, and the temperature is kept for 2-3 hours.

[0033] Preferably, in step (4), the adhesive is a cement adhesive.

[0034] The invention discloses a pollution-flashover-proof and impact-resistant tempered glass insulator, which is obtained through the above-mentioned processing technology.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The invention firstly mixes the formulated amount of silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide and nano boron nitride uniformly, melts them and obtains a molten liquid; then slowly injects the molten liquid into a preheated mold in a nitrogen environment, shapes it, demolds it and obtains a blank; performs a primary nitriding treatment, a pulse magnetic field treatment, a tempering treatment, a heat treatment and a secondary nitriding treatment to obtain a tempered glass part; finally, the iron cap, the tempered glass part and the steel foot are glued together by an adhesive to obtain a tempered glass insulator. The tempered glass insulator has excellent anti-pollution flashover and impact resistance.

[0037] The raw materials of the tempered glass of the present invention are mainly silicon dioxide, supplemented by sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide and nano boron nitride, which work synergistically to ensure that the tempered glass has good impact resistance.

[0038] The present invention sequentially performs primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, and secondary nitriding treatment on the blank, thereby obtaining a tempered glass piece. The order of these treatment processes cannot be reversed. The primary nitriding treatment and pulse magnetic field treatment are beneficial to microscopic homogenization, improving the tempering effect, improving the impact resistance of the tempered glass piece, and are beneficial to surface structure optimization and improving the anti-pollution flashover effect; after the tempering treatment, heat treatment and secondary nitriding treatment are performed to further optimize the internal and surface results, and further improve the impact resistance and anti-pollution flashover performance of the tempered glass piece. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Unless otherwise specified, all commodities in this invention are purchased through market channels.

[0041] Example 1

[0042] A processing technology for anti-pollution flashover and impact-resistant tempered glass insulators, the specific steps are as follows:

[0043] (1) firstly, uniformly mix silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide, and nano boron nitride in a formulated amount, and melt the mixture to obtain a molten liquid;

[0044] The formula composition is: 6kg silicon dioxide, 0.8kg sodium carbonate, 0.5kg calcium oxide, 0.5kg magnesium oxide, 0.4kg cerium dioxide, 0.2kg niobium trioxide, 0.1kg scandium trioxide, 0.1kg tungsten carbide, 0.1kg nano boron nitride;

[0045] The melting temperature is 1300°C and the temperature is kept at the melting temperature for 30 minutes;

[0046] (2) then slowly injecting the molten liquid into a preheated mold under a nitrogen environment, forming, demolding, and obtaining a blank;

[0047] The mold is preheated to 700°C, the molding temperature is 500°C, and the holding time is 60 minutes;

[0048] (3) primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, secondary nitriding treatment to obtain a tempered glass piece;

[0049] The specific method of the primary nitriding treatment is as follows: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 500°C at 8°C / min, kept at this temperature for 1 hour, the temperature is raised to 580°C at 2°C / min, kept at this temperature for 2 hours, and then cooled to room temperature along with the furnace;

[0050] The process conditions of pulse magnetic field treatment were as follows: pulse magnetic field frequency 0.05 Hz, magnetic field 4 T, and treatment time 30 min;

[0051] The process conditions of the tempering treatment are: in the tempering machine, the tempering is carried out at a speed of 150-200 r / min, the upper air pressure is 0.1 MPa, and the lower air pressure is 0.05 MPa;

[0052] The process flow of heat treatment is:

[0053] (a) Rotation speed 280r / min, heating at 7℃ / min to 700℃, keeping temperature for 30 minutes;

[0054] (b) Rotate at 220 r / min, cool to 640°C at 2°C / min, and keep warm for 50 min;

[0055] (c) rotating speed 180 r / min, heating at 5 °C / min to 750 °C, keeping temperature for 60 min;

[0056] (d) Rotate at 220 r / min and keep warm for 2 hours;

[0057] (e) cooling naturally to room temperature;

[0058] The specific method of secondary nitriding treatment is as follows: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 550°C at 5°C / min, and the temperature is kept for 2 hours;

[0059] (4) Finally, the iron cap, the tempered glass part and the steel foot are glued together using cement adhesive (purchased from Kehui (Shanghai) New Material Technology Co., Ltd.) to obtain the tempered glass insulator.

[0060] Example 2

[0061] A processing technology for anti-pollution flashover and impact-resistant tempered glass insulators, the specific steps are as follows:

[0062] (1) firstly, uniformly mix silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide, and nano boron nitride in a formulated amount, and melt the mixture to obtain a molten liquid;

[0063] The formula composition is: 7kg silicon dioxide, 1kg sodium carbonate, 0.6kg calcium oxide, 0.6kg magnesium oxide, 0.5kg cerium dioxide, 0.3kg niobium trioxide, 0.2kg scandium trioxide, 0.2kg tungsten carbide, 0.2kg nano boron nitride;

[0064] The melting temperature is 1400°C and the temperature is kept at the melting temperature for 40 minutes;

[0065] (2) then slowly injecting the molten liquid into a preheated mold under a nitrogen environment, forming, demolding, and obtaining a blank;

[0066] Preheat the mold to 800°C. The molding temperature is 600°C and the holding time is 70 minutes;

[0067] (3) primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, secondary nitriding treatment to obtain a tempered glass piece;

[0068] The specific method of the primary nitriding treatment is as follows: in the nitriding furnace, ammonia is introduced, the temperature is raised to 520°C at 10°C / min, kept at this temperature for 2 hours, the temperature is raised to 600°C at 3°C / min, kept at this temperature for 3 hours, and then cooled to room temperature along with the furnace;

[0069] The process conditions of pulse magnetic field treatment were as follows: pulse magnetic field frequency 0.07 Hz, magnetic field 6 T, and treatment time 40 min;

[0070] The process conditions of the tempering treatment are: in the tempering machine, the tempering is carried out at a speed of 200r / min, the upper air pressure is 0.12MPa, and the lower air pressure is 0.07MPa;

[0071] The process flow of heat treatment is:

[0072] (a) Rotate at 300 r / min, heat at 8°C / min to 720°C, and keep at this temperature for 40 min;

[0073] (b) Rotate at 250 r / min, cool to 660°C at 3°C / min, and keep at this temperature for 60 min;

[0074] (c) rotating speed 200 r / min, heating at 6°C / min to 780°C, and keeping at this temperature for 80 min;

[0075] (d) Rotate at 250 r / min and keep warm for 3 hours;

[0076] (e) cooling naturally to room temperature;

[0077] The specific method of secondary nitriding treatment is as follows: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 580°C at 6°C / min, and the temperature is kept for 3 hours;

[0078] (4) Finally, the iron cap, the tempered glass part and the steel foot are glued together using cement adhesive (purchased from Kehui (Shanghai) New Material Technology Co., Ltd.) to obtain the tempered glass insulator.

[0079] Example 3

[0080] A processing technology for anti-pollution flashover and impact-resistant tempered glass insulators, the specific steps are as follows:

[0081] (1) firstly, uniformly mix silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide, and nano boron nitride in a formulated amount, and melt the mixture to obtain a molten liquid;

[0082] The formula composition is: 6kg silicon dioxide, 1kg sodium carbonate, 0.5kg calcium oxide, 0.6kg magnesium oxide, 0.4kg cerium dioxide, 0.3kg niobium trioxide, 0.1kg scandium trioxide, 0.2kg tungsten carbide, 0.1kg nano boron nitride;

[0083] The melting temperature is 1400°C and the temperature is kept at the melting temperature for 30 minutes;

[0084] (2) then slowly injecting the molten liquid into a preheated mold under a nitrogen environment, forming, demolding, and obtaining a blank;

[0085] Preheat the mold to 800°C. The molding temperature is 500°C and the holding time is 70 minutes;

[0086] (3) primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, secondary nitriding treatment to obtain a tempered glass piece;

[0087] The specific method of primary nitriding treatment is as follows: in the nitriding furnace, introduce ammonia gas, heat up to 520°C at 8°C / min, keep warm for 1 hour, heat up to 580°C at 3°C / min, keep warm for 3 hours, and cool to room temperature with the furnace;

[0088] The process conditions of pulse magnetic field treatment were as follows: pulse magnetic field frequency 0.05 Hz, magnetic field 6 T, and treatment time 30 min;

[0089] The process conditions of the tempering treatment are: in the tempering machine, the tempering is carried out at a speed of 200r / min, the upper air pressure is 0.1MPa, and the lower air pressure is 0.07MPa;

[0090] The process flow of heat treatment is:

[0091] (a) Rotation speed 280r / min, heating at 8℃ / min to 700℃, keeping temperature for 40 minutes;

[0092] (b) Rotate at 220 r / min, cool to 640°C at 3°C / min, and keep warm for 60 min;

[0093] (c) rotating speed 180 r / min, heating at 6 °C / min to 750 °C, keeping temperature for 80 min;

[0094] (d) Rotate at 220 r / min and keep warm for 3 hours;

[0095] (e) cooling naturally to room temperature;

[0096] The specific method of secondary nitriding treatment is as follows: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 580°C at 5°C / min, and the temperature is kept for 2 hours;

[0097] (4) Finally, the iron cap, the tempered glass part and the steel foot are glued together using cement adhesive (purchased from Kehui (Shanghai) New Material Technology Co., Ltd.) to obtain the tempered glass insulator.

[0098] Example 4

[0099] A processing technology for anti-pollution flashover and impact-resistant tempered glass insulators, the specific steps are as follows:

[0100] (1) firstly, uniformly mix silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide, and nano boron nitride in a formulated amount, and melt the mixture to obtain a molten liquid;

[0101] The formula composition is: 6.5kg silicon dioxide, 0.9kg sodium carbonate, 0.55kg calcium oxide, 0.55kg magnesium oxide, 0.45kg cerium dioxide, 0.25kg niobium trioxide, 0.15kg scandium trioxide, 0.15kg tungsten carbide, 0.15kg nano boron nitride;

[0102] The melting temperature is 1350°C and the temperature is kept at the melting temperature for 35 minutes;

[0103] (2) then slowly injecting the molten liquid into a preheated mold under a nitrogen environment, forming, demolding, and obtaining a blank;

[0104] Preheat the mold to 750°C. The molding temperature is 550°C and the holding time is 65 minutes;

[0105] (3) primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, secondary nitriding treatment to obtain a tempered glass piece;

[0106] The specific method of primary nitriding treatment is as follows: in the nitriding furnace, introduce ammonia gas, heat up to 510°C at 9°C / min, keep warm for 1 hour, heat up to 590°C at 2°C / min, keep warm for 2 hours, and cool to room temperature with the furnace;

[0107] The process conditions of pulse magnetic field treatment were as follows: pulse magnetic field frequency 0.06 Hz, magnetic field 5 T, and treatment time 35 min;

[0108] The process conditions of tempering treatment are: in the tempering machine, tempering is carried out at a speed of 170r / min, the upper air pressure is 0.11MPa, and the lower air pressure is 0.06MPa;

[0109] The process flow of heat treatment is:

[0110] (a) Rotation speed 290r / min, heating at 7.5℃ / min to 710℃, keeping temperature for 35 minutes;

[0111] (b) Rotate at 240 r / min, cool to 650°C at 2.5°C / min, and keep at this temperature for 55 min;

[0112] (c) rotating speed 190 r / min, heating at 5.5 °C / min to 770 °C, keeping temperature for 70 min;

[0113] (d) Rotate at 240 r / min and keep warm for 2.5 hours;

[0114] (e) cooling naturally to room temperature;

[0115] The specific method of secondary nitriding treatment is as follows: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 570°C at 6°C / min, and the temperature is kept for 2.5 hours;

[0116] (4) Finally, the iron cap, the tempered glass part and the steel foot are glued together using cement adhesive (purchased from Kehui (Shanghai) New Material Technology Co., Ltd.) to obtain the tempered glass insulator.

[0117] Comparative Example 1

[0118] The formula composition omits cerium dioxide.

[0119] The rest is the same as in Example 1.

[0120] Comparative Example 2

[0121] Niobium trioxide is omitted from the formula composition.

[0122] The rest is the same as in Example 1.

[0123] Comparative Example 3

[0124] Scandium trioxide is omitted from the formula composition.

[0125] The rest is the same as in Example 1.

[0126] Comparative Example 4

[0127] The formula composition omits tungsten carbide.

[0128] The rest is the same as in Example 1.

[0129] Comparative Example 5

[0130] The formula composition omits nano boron nitride.

[0131] The rest is the same as in Example 1.

[0132] Comparative Example 6

[0133] Omit the nitriding treatment once.

[0134] The rest is the same as in Example 1.

[0135] Comparative Example 7

[0136] The pulsed magnetic field treatment was omitted.

[0137] The rest is the same as in Example 1.

[0138] Comparative Example 8

[0139] Omit heat treatment.

[0140] The rest is the same as in Example 1.

[0141] Comparative Example 9

[0142] The secondary nitriding treatment is omitted.

[0143] The rest is the same as in Example 1.

[0144] Test example

[0145] The anti-pollution flashover and anti-impact performance of the tempered glass parts of the insulators obtained in Examples 1 to 4 and Comparative Examples 1 to 9 were investigated respectively, and the specific methods are as follows:

[0146] 1. Anti-pollution flashover performance: Refer to GB / T 4585-2024 "Artificial pollution test for high-voltage porcelain and glass insulators for AC systems" to test the maximum tolerable salinity under 150kV conditions.

[0147] 2. Impact resistance: The fracture toughness is tested using the single edge notched beam method (SENB).

[0148] Table 1. Performance investigation of tempered glass insulators

[0149] <![CDATA[Maximum tolerable salinity (kg / m 3 )]]> Fracture toughness(MPa) Example 1 224 87 Example 2 224 89 Example 3 224 92 Example 4 224 96 Comparative Example 1 160 65 Comparative Example 2 160 69 Comparative Example 3 112 69 Comparative Example 4 112 71 Comparative Example 5 112 70 Comparative Example 6 80 75 Comparative Example 7 80 76 Comparative Example 8 80 75 Comparative Example 9 80 74

[0150] It can be seen from Table 1 that the insulators obtained in Examples 1 to 4 have a high maximum tolerable salinity, indicating that they have excellent anti-pollution flashover performance, and a high fracture toughness, indicating that they have excellent impact resistance.

[0151] The formula composition of Comparative Example 1 omits cerium dioxide, the formula composition of Comparative Example 2 omits niobium trioxide, the formula composition of Comparative Example 3 omits scandium trioxide, the formula composition of Comparative Example 4 omits tungsten carbide, the formula composition of Comparative Example 5 omits nano-boron nitride, Comparative Example 6 omits the primary nitriding treatment, Comparative Example 7 omits the pulse magnetic field treatment, Comparative Example 8 omits the heat treatment, and Comparative Example 9 omits the secondary nitriding treatment. The anti-pollution flashover performance and the impact resistance performance are significantly deteriorated, indicating that the formula composition of the tempered glass piece and the primary nitriding treatment and pulse magnetic field treatment of the blank before tempering treatment, the heat treatment after tempering treatment, the secondary nitriding treatment and other steps work synergistically to optimize the structure of the tempered glass piece and promote the improvement of the anti-pollution flashover performance and the impact resistance performance.

[0152] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A processing technology for anti-pollution flashover and impact-resistant tempered glass insulators, characterized in that: The specific steps are as follows: (1) firstly, uniformly mix silicon dioxide, sodium carbonate, calcium oxide, magnesium oxide, cerium dioxide, niobium trioxide, scandium trioxide, tungsten carbide and nano boron nitride in a formulated amount, and melt the mixture to obtain a molten liquid; (2) then slowly injecting the molten liquid into a preheated mold under a nitrogen environment, forming, demolding, and obtaining a blank; (3) primary nitriding treatment, pulse magnetic field treatment, tempering treatment, heat treatment, secondary nitriding treatment to obtain a tempered glass piece; (4) Finally, the iron cap, the tempered glass piece and the steel foot are glued together using adhesive to obtain the tempered glass insulator.

2. The processing technology according to claim 1, characterized in that: In step (1), the formula composition is, by weight: 60-70 parts of silicon dioxide, 8-10 parts of sodium carbonate, 5-6 parts of calcium oxide, 5-6 parts of magnesium oxide, 4-5 parts of cerium dioxide, 2-3 parts of niobium trioxide, 1-2 parts of scandium trioxide, 1-2 parts of tungsten carbide, and 1-2 parts of nano boron nitride.

3. The processing technology according to claim 1, characterized in that: In step (1), the melting temperature is 1300-1400° C., and the melting temperature is maintained for 30-40 minutes.

4. The processing technology according to claim 1, characterized in that: In step (2), the mold is preheated to 700-800°C; The molding temperature is 500-600°C and the holding time is 60-70 minutes.

5. The processing technology according to claim 1, characterized in that: In step (3), the specific method of the primary nitriding treatment is: in the nitriding furnace, ammonia is introduced, the temperature is raised to 500-520°C at 8-10°C / min, and the temperature is kept for 1-2 hours, the temperature is raised to 580-600°C at 2-3°C / min, and the temperature is kept for 2-3 hours, and the furnace is cooled to room temperature.

6. The processing technology according to claim 1, characterized in that: In step (3), the process conditions of the pulse magnetic field treatment are: pulse magnetic field frequency 0.05-0.07 Hz, magnetic field 4-6 T, and treatment time 30-40 minutes.

7. The processing technology according to claim 1, characterized in that: In step (3), the process conditions of the tempering treatment are: in the tempering machine, tempering is carried out at a rotation speed of 150 to 200 r / min, the upper wind pressure is 0.1 to 0.12 MPa, and the lower wind pressure is 0.05 to 0.07 MPa.

8. The processing technology according to claim 1, characterized in that: In step (3), the process flow of heat treatment is as follows: (a) Rotate at 280-300 r / min, heat at 7-8 °C / min to 700-720 °C, and keep warm for 30-40 minutes; (b) rotating speed 220-250 r / min, cooling at 2-3°C / min to 640-660°C, keeping warm for 50-60 minutes; (c) rotating at 180-200 r / min, heating at 5-6°C / min to 750-780°C, and keeping at this temperature for 60-80 minutes; (d) Rotate at 220-250 r / min and keep warm for 2-3 hours; (e) Cool naturally to room temperature.

9. The processing technology according to claim 1, characterized in that: In step (3), the specific method of the secondary nitriding treatment is: in the nitriding furnace, ammonia gas is introduced, the temperature is raised to 550-580° C. at a rate of 5-6° C. / min, and the temperature is kept for 2-3 hours. 10.Anti-pollution flashover and impact-resistant tempered glass insulator, characterized in that: The invention is obtained by the processing technology described in any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of icing flashover-resistant glass insulator adopting self-repairing super-hydrophobic coating

    CN122158287A